1992
DOI: 10.1101/gad.6.9.1589
|View full text |Cite
|
Sign up to set email alerts
|

Pax-5 encodes the transcription factor BSAP and is expressed in B lymphocytes, the developing CNS, and adult testis.

Abstract: BSAP has been identified previously as a transcription factor that is expressed at early, but not late, stages of B-cell differentiation. Biochemical purification and cDNA cloning has now revealed that BSAP belongs to the family of paired domain proteins. BSAP is encoded by the Pax-5 gene and has been highly conserved between human and mouse. An intact paired domain was shown to be both necessary and sufficient for DNA binding of BSAP. Binding studies with several BSAP recognition sequences demonstrated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
375
2
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(388 citation statements)
references
References 50 publications
9
375
2
2
Order By: Relevance
“…The identi®cation of an ATTA motif as an important binding sequence in this promoter is remarkable in several aspects. First, it might explain the failure of Pax5 to activate the Bcl-x promoter, since Pax5 contains only a partial homeobox (Adams et al, 1992). Second, it has recently been suggested that the oncogenic potential of PAX3/FKHR requires the homeodomain, but not the paired box domain (Lam et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The identi®cation of an ATTA motif as an important binding sequence in this promoter is remarkable in several aspects. First, it might explain the failure of Pax5 to activate the Bcl-x promoter, since Pax5 contains only a partial homeobox (Adams et al, 1992). Second, it has recently been suggested that the oncogenic potential of PAX3/FKHR requires the homeodomain, but not the paired box domain (Lam et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition to its expression in B cells, PAX5 protein and/or mRNA has been reported to be expressed in normal and neoplastic cell types in the central nervous system, testis and bladder. 3,[10][11][12][13][14][15] B-cell malignancies may express PAX5 in the absence of expression of other pan-B-cell markers, suggesting that the inclusion of PAX5 in a panel of antibodies to assess undifferentiated malignant neoplasms may have diagnostic benefit. To address this possibility, we studied examples previously diagnosed as undifferentiated malignant neoplasms for PAX5 expression by immunohistologic methods.…”
mentioning
confidence: 99%
“…1,2 PAX5 protein is expressed as a nuclear marker in B-lineage cells that span the differentiation spectrum from precursor B cells to early plasma cells. 3,4 The expression of PAX5 protein is also a useful lineage-specific marker in hematopoietic neoplasms arising from B cells. [5][6][7][8] Staining for PAX5 has additional utility in the diagnosis of B-cell malignancies that lack expression of commonly used pan-B-cell markers such as CD20 and CD79a.…”
mentioning
confidence: 99%
“…A combination of the pT7TS-derived ␤-globin UTRs with the pCS2 backbone nevertheless resulted in decreased activity of the injected mRNA (van der Velden et al, 2001), thus indicating that the effects of the UTRs are not additive. We compared mRNA derived from pT7TS and pCS2 to that of the typical cell culture expression vector pKW10 (Adams et al, 1992), which has an architecture similar to pCS2 [CMV promoter, artificial UTRs, and SV40 early poly(A) signal]. Both transcription vectors positively affected the activity of injected mRNA in early embryos ( Fig.…”
Section: Stability Of the Injected Mrnamentioning
confidence: 99%
“…The construct "KW luc" is a derivative of the expression vector pKW10 (Adams et al, 1992) containing firefly luciferase as insert. "Pax2 luc" contains the 5Ј and 3Ј UTRs of the zebrafish Pax2 gene within the pKW10 backbone.…”
Section: Dna Constructsmentioning
confidence: 99%